A glass polyalkenoate cement carrier for bone morphogenetic proteins - Alhalawani, A.M.F.; Rodriguez, O.; Curran, D.J.; Co, R.; Kieran, S.; Arshad, S.; Keenan, T.J.; Wren, A.W.; Crasto, G.; Peel, S.A.F.; Towler, M.R. (2015)
This work considers a glass polyalkenoate cement (GPC)-based carrier for the effective delivery of bone morphogenetic proteins (BMPs) at an implantation site. A 0.12 CaO-0.04 SrO-0.36 ZnO-0.48 SiO2 based glass and poly(acrylic acid) (PAA, Mw 213,000) were employed for the fabrication of the GPC. The media used for the water source in the GPC reaction was altered to produce a series of GPCs. The GPC liquid media was either 100 distilled water with additions of albumin at 0, 2, 5 and 8 wt of the glass content, 100 formulation buffer (IFB), and 100 BMP (150 mu g rhBMP-2/ml IFB). Rheological properties, compressive strength, ion release profiles and BMP release were evaluated. Working times (T-w) of the formulated GPCs significantly increased with the addition of 2 albumin and remained constant with further increases in albumin content or IFB solutions. Setting time (T-s) experienced an increase with 2 and 5 albumin content, but a decrease with 8 albumin. Changing the liquid source to IFB containing 5 albumin had no significant effect on T-s compared to the 8 albumin-containing BT101. Replacing the albumin with IFB/BMP-2 did not significantly affect T-w. However, T-s increased for the BT101BMP-2 containing GPCs, compared to all other samples. The compressive strength evaluated 1 day post cement mixing was not affected significantly by the incorporation of BMPs, but the ion release did increase from the cements, particularly for Zn and Sr. The GPCs released BMP after the first day, which decreased in content during the following 6 days. This study has proven that BMPs can be immobilized into GPCs and may result in novel materials for clinical applications.